Stress management on the sustainability of traditional food MSME in East Priangan - Andriati, Yumi Sri; Marlina, Lina (Journal of Economics and Business Letters, 2023)
MSME actors greatly encourage the country's economy and need government attention so that this sector's business is long-lived. However, the reality is that in running a business, MSME actors have yet to be accompanied by solid resource capabilities, which makes them vulnerable to bankruptcy. Expectations of increasing business in terms of turnover, determining strategies and cooperation are challenged by financial pressures, market competition, and operational challenges that can cause stress. It is necessary to help overcome this immediately so that the sustainability of the SME business is not disrupted. This research analyzes SME business sustainability through stress management, focusing on handling problems, emotions, and unproductive actions. The quantitative research method with exploratory survey involved traditional food SMEs in East Priangan. Data were collected through questionnaires and observations. The results showed that SMEs focused on handling problems in managing stress. It is proven that problem-focused handling contributes significantly to business sustainability. Meanwhile, emotion-focused handling and focusing on unproductive handling do not contribute to business sustainability.